Enhancement of Mechanical Properties of Aluminum and 2124 Aluminum Alloy by the Addition of Quasicrystalline Phases - Wolf,Witor (2016)
A structural and mechanical characterization of pure aluminum and 2124 T6 aluminum alloy reinforced with quasicrystalline phases of composition Al65Cu20Fe15 and Al70.5Pd21Mn8.5 (%at.) were performed. The quasicrystalline phases were synthesized by arc melting and then milled to produce powder of the alloys, which were then mechanical mixed with the starting powders of aluminum and 2124 aluminum alloy. The composites were produced by hot extrusion of a mechanical mixture containing 20% (%wt.) of the reinforcing phases on the metallic matrix. The structural characterization of the composites was carried out by X-ray diffraction, scanning electron microscopy and transmission electron microscopy. Mechanical characterization was carried out by Vickers hardness measurements and torsion tests at room temperature. The pure aluminum/quasicrystal composite showed the presence of the same phases from the starting powder mixture while for the 2124 aluminum alloy/Al65Cu20Fe15 the quasicrystalline phase transformed to the tetragonal ω-Al7Cu2Fe during the solution heat treatment. Mechanical strength of the composites presented a substantial increase in comparison to the original matrix metal. While the equivalent ultimate tensile strength of the Al/quasicrystal composites reached values up to 215MPa and Vickers hardness up to 60HV, the 2124/quasicrystal composites reached values up to 670MPa and Vickers hardness up to 190HV.